Randomized comparative study of conventional minilaparoscopy (5mm) versus modern minilaparoscopy (2.9mm) in patients of infertility - Roy, Kallol Kumar; Jahagirdar, Nandini Joshi nee; Subbaiah, Murali; Jain, Sunesh Kumar; Sharma, J. B.; Singh, Neeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: To compare diagnostic conventional minilaparoscopy (5mm) with diagnostic modern minilaparoscopy (2.9mm) in patients of infertility in terms of operating time, post-operative pain, hospital stay. Methods: A prospective randomized comparative study was done in a tertiary care centre involving eighty patients of infertility undergoing diagnostic laparoscopy. Diagnostic laparoscopy was done using 5mm laparoscope (Conventional minilaparoscope-Group I) in 40 patients and using 2.9mm laparoscope (Modern minilaparoscope-Group II) in 40 patients. Operating time was measured from the point of skin incision to closure, post op pain was assessed with VAS scoring system, total hours of hospital stay from shifting to day care recovery ward till discharge was noted. Results: Both conventional minilaroscope and modern minilaparoscopes were comparable to each other. Operating time in both groups was similar (7.7min in Group I vs 8.7min in Group II). In both groups, there was no statistically significant difference in post-operative pain as assessed by VAS scoring System (39 in Group I vs 38 in Group II had mild post-op pain and 1 in Group I vs 2 in Group II had moderate pain). The difference in duration of post-op hospital stay in both Group I and group II was not statistically significant (3.5 hours vs 3.3 hours). Conclusions: Both conventional minilaparoscopy (5mm laparoscope) and modern miniaparoscopy (2.9mm laparoscope) are comparable with respect operating time, post-op pain, hospital stay. Modern minilaparoscope is no better than conventional minilaparoscope.